Therapeutic Strategies for Attenuation of Retinal Ganglion Cell Injury in Optic Neuropathies: Concepts in Translational Research and Therapeutic Implications - Lin Fu (BioMed Research International, 2019)
Retinal ganglion cell (RGC) death is the central and irreversible endpoint of optic neuropathies. Current management of optic neuropathies and glaucoma focuses on intraocular pressure-lowering treatment which is insufficient. As such, patients are effectively condemned to irreversible visual impairment. This review summarizes experimental treatments targeting RGCs over the last decade. In particular, we examine the various treatment modalities and determine their viability and limitations in translation to clinical practice. Experimental RGC treatment can be divided into (1) cell replacement therapy, (2) neuroprotection, and (3) gene therapy. For cell replacement therapy, difficulties remain in successfully integrating transplanted RGCs from various sources into the complex neural network of the human retina. However, there is significant potential for achieving full visual restoration with this technique. Neuroprotective strategies, in the form of pharmacological agents, nutritional supplementation, and neurotrophic factors, are viable strategies with encouraging results from preliminary noncomparative interventional case series. It is important to note, however, that most published studies are focused on glaucoma, with few treating optic neuropathies of other etiologies. Gene therapy, through the use of viral vectors, has shown promising results in clinical trials, particularly for diseases with specific genetic mutations like Leber’s hereditary optic neuropathy. This treatment technique can be further extended to nonhereditary diseases, through transfer of genes promoting cell survival and neuroprotection. Crucially though, for gene therapy, teratogenicity remains a significant issue in translation to clinical practice.